2021
DOI: 10.3390/ijms22063275
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Mesenchymal Stem Cell Treatment Improves Myelination Impaired by Global Perinatal Asphyxia in Rats

Abstract: The effect of perinatal asphyxia (PA) on oligodendrocyte (OL), neuroinflammation, and cell viability was evaluated in telencephalon of rats at postnatal day (P)1, 7, and 14, a period characterized by a spur of neuronal networking, evaluating the effect of mesenchymal stem cell (MSCs)-treatment. The issue was investigated with a rat model of global PA, mimicking a clinical risk occurring under labor. PA was induced by immersing fetus-containing uterine horns into a water bath for 21 min (AS), using sibling-caes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 116 publications
1
9
0
Order By: Relevance
“…The effect of PA on mature OLs (MBP positive cells), astrocytes (GFAP positive cells), and microglia (Ionized calcium-binding adaptor molecule 1, Iba-1 positive cells) was further investigated in the same telencephalic coronal section of AS and CS animals taken at P7. We observed that the number of MBP cells/mm 3 was decreased in AS compared to that in CS animals (by ~50%), without any effect on astrocytes and microglia markers [ 68 ], supporting the view that OLs are the most vulnerable glial cells to hypoxia-reoxygenation injury, at least in the examined brain regions. In the external capsule and corpus callosum, TUNEL/MBP-DAPI/mm 3 quantification was increased in AS compared to the CS condition, suggesting that PA increases OLs specific cell death, but also disrupts oligodendroglial lineage maturation, explaining the significant decrease observed in the number of OLs.…”
Section: Effect Of Pa On Oligodendrocyte Maturationsupporting
confidence: 63%
See 4 more Smart Citations
“…The effect of PA on mature OLs (MBP positive cells), astrocytes (GFAP positive cells), and microglia (Ionized calcium-binding adaptor molecule 1, Iba-1 positive cells) was further investigated in the same telencephalic coronal section of AS and CS animals taken at P7. We observed that the number of MBP cells/mm 3 was decreased in AS compared to that in CS animals (by ~50%), without any effect on astrocytes and microglia markers [ 68 ], supporting the view that OLs are the most vulnerable glial cells to hypoxia-reoxygenation injury, at least in the examined brain regions. In the external capsule and corpus callosum, TUNEL/MBP-DAPI/mm 3 quantification was increased in AS compared to the CS condition, suggesting that PA increases OLs specific cell death, but also disrupts oligodendroglial lineage maturation, explaining the significant decrease observed in the number of OLs.…”
Section: Effect Of Pa On Oligodendrocyte Maturationsupporting
confidence: 63%
“…40 min after delivery (accounted from the time the uterine horns are excised from the abdominal cavity, cutting the uterine artery and venous at the level of the cervix), surviving pups are evaluated with an Apgar scale adapted to rats, monitoring the body weight, sex, color of the skin, respiratory frequency, gasping, vocalization, muscular rigidity and spontaneous movements [ 66 , 67 ]. The evaluation can be extended to several days after delivery [ 68 , 69 ]. The Apgar evaluation is critical for this experimental model because it assesses the extent of the insult since severity is directly correlated with the rate of survival and recovery by the pups of a litter.…”
Section: An Experimental Model Of Global Pa In Ratsmentioning
confidence: 99%
See 3 more Smart Citations